Combination of surface with bulk: hybrids of supercapacitors with Li-ion batteries - Y. A. Maletin; S. I. Chernukhin; N. G. Stryzhakova; S. G. Kozachkov (Хімія, фізика та технологія поверхні)
As it turns out, the right combination of Li-ion and supercapacitor ingredients in both the positive and negative electrodes, as well as in the electrolyte, can significantly improve the characteristics of such a hybridized power supply as compared with “parent” systems. While Li-ion components provide large volumetric energy, the high surface area of nanoporous carbon borrowed from supercapacitor technology provides fast charge-discharge of the corresponding electric double layer and facilitates the intercalation-deintercalation processes in the Li-ion components. This full hybridization of the system can increase the energy density by 10 times that of a supercapacitor while maintaining the relatively high power density, long cycle life, and fast charging characteristics of supercapacitors. In addition, charge-discharge curves and low self-discharge currents become similar to those of Li-ion batteries. Such power supplies with a specific energy of 60+ Wh/kg, a full charge within 5–6 minutes and more than 30 K full charge-discharge cycles can be successfully used, for example, in urban transport or robotics in warehouses where the range is less critical than fast charging capability, long service life and safe operation. This article discusses the methods of full hybridization and the achieved characteristics of electrochemical systems “supercapacitor and Li-ion battery”. Special attention is paid to the “interaction” of the activated carbon surface with the channels in the bulk lithiated metal-oxide material of the electrodes to accelerate the charge-discharge processes.